3-Abstracts Communications Orales -Imagerie Pédiatrique_ JRANF 2024_JAIM 2024_16.3 - Moustapha H; DONGMO FOMEKONG Sylviane; MOULION TAPOUH Jean-Roger; MOIFO Boniface; Alassane KOUMA; Nfally BADJI; KOUANDONGUI BANGUE SONGROU Francky; Nfally BADJI; S GUIDAH; GANIOU TIDJANI Kabirou; et al. (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2024)
3-Abstracts Communications Orales -Imagerie Pédiatrique_ JRANF 2024_JAIM 2024_16.3